REMOTE SURVEILLANCE OF SHELL STRUCTURE LOAD-BEARING CAPACITY - Stupishin, Leonid Yulianovich; Masalov, Alexandr Vasilyevich; Altukhov, Feodor (Journal of Applied Engineering Science, 2017)
The problem background of load-bearing capacity remote surveillance was presented. The issues of continuous automatic surveillance of building and structure condition arrangement are discussed in the article. Principles and basic approaches to surveillance arrangement are considered in the context of solving the problem for Kursk State Circus building reconstruction, which was damaged by fire and environmental impacts occurred after several year of being in no operation. Surveillance parameters - displacement, relative humidity, temperature, heat flow and means of measurement are discussed The automated system for building surveillance, maintenance and data storage is considered. Load-bearing capacity remote surveillance should be the essential part of this automated system.
Keywords: Remote surveillance of structure conditions; Dome; Automated control system; Visual monitoring; Shallow shells